Reduction in World Health Organization Risk Drinking Levels and Cardiovascular Disease. (3rd July 2020) - Knox, Justin; Scodes, Jennifer; Witkiewitz, Katie; Kranzler, Henry R.; Mann, Karl; O'Malley, Stephanie S.; Wall, Melanie; Anton, Raymond; Hasin, Deborah S.; ,
Abstract : Background: Reductions in World Health Organization (WHO) risk drinking levels have recently been shown to lower the risk of multiple adverse health outcomes, but prior work has not examined reductions in WHO risk drinking levels in relation to cardiovascular disease (CVD), the leading cause of death for men and women in the United States and of global mortality. This study examined associations between reductions in WHO risk drinking levels and subsequent risk for CVD. Methods: In a US national survey, 1, 058 very‐high‐risk and high‐risk drinkers participated in Wave 1 interviews (2001 to 2002) and Wave 2 follow‐ups (2004 to 2005). Self‐reported CVD history that was communicated to the participant by a doctor or other healthcare professionals included arteriosclerosis, hypertension, angina, tachycardia, or myocardial infarction. We used logistic regression to estimate adjusted odds ratios (aOR) evaluating relationships between ≥2‐level reductions in WHO risk drinking levels from Wave 1 to Wave 2 and the risk of Wave 2 CVD, controlling for baseline characteristics. Results: Reductions of ≥2 WHO risk drinking levels were associated with significantly lower odds of CVD in individuals who at Wave 1 were very‐high‐risk (aOR = 0.58 [0.41 to 0.80]) or high‐risk drinkers (aOR = 0.81 [0.70 to 0.94]). Interaction terms showed that this relationship varied by age. Among individuals >40 years old at Wave 1, reductions of ≥2 WHO risk drinking levels were associated with significantly lower odds of CVD among very‐high‐risk drinkers (aOR = 0.42 [0.28 to 0.63]) but not high‐risk drinkers ( p = 0.50). Among individuals ≤40 years old at Wave 1, reductions of ≥2 WHO risk drinking levels were associated with significantly lower odds of CVD among high‐risk drinkers (aOR = 0.50 [0.37 to 0.69]) but not very‐high‐risk drinkers ( p = 0.27). Conclusions: These results show that reductions in WHO risk drinking levels are associated with reduced CVD risk among very‐high‐risk and high‐risk drinkers in the US general population, and provide further evidence that reducing high levels of drinking provides important benefit across multiple clinical domains. Abstract : This study showed that reductions of two or more WHO risk drinking levels were associated with significantly lower odds of subsequent cardiovascular disease among very‐high‐risk and high‐risk drinkers in the US general population. These findings provide further evidence that reducing high levels of drinking, including to levels that are not complete abstinence, provides important benefit across multiple clinical domains. WHO risk drinking levels can provide useful drinking goals to be considered with patients, and valid clinical trial outcome indicators.